2003
DOI: 10.1242/dev.00697
|View full text |Cite
|
Sign up to set email alerts
|

γ-Secretase activity is dispensable for mesenchyme-to-epithelium transition but required for podocyte and proximal tubule formation in developing mouse kidney

Abstract: Notch signaling is involved in pronephros development inXenopus and in glomerulogenesis in mice. However, owing to early lethality in mice deficient for some Notch pathway genes and functional redundancy for others, a role for Notch signaling during early stages of metanephric development has not been defined. Using an antibody specific to the N-terminal end of γ-secretase-cleaved Notch1, we found evidence for Notch1 activation in the comma and S-shaped bodies of the mouse metanephros. We therefore cultured mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
174
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(192 citation statements)
references
References 68 publications
15
174
3
Order By: Relevance
“…The absolute cell numbers with control Fc are ϳ5-fold higher than that with Delta4-Fc, and the fold increases in the cell number after the 3-wk culture were 45.7 Ϯ 31.6-fold (n ϭ 11). To confirm that the NK cell differentiation was Notch dependent, we added a ␥-secretase inhibitor, DAPT, which strongly inhibits ligand-dependent Notch activation (24,25). The cells cultured on Delta4-Fc-coated plates in the presence of DAPT had the same immunophenotype as those cultured on the control Fc-coated plates and did not give rise to NK cells (Fig.…”
Section: Human Cb Cd34 ϩ and Cd133 ϩ Cells Gave Rise To Functional Nkmentioning
confidence: 99%
“…The absolute cell numbers with control Fc are ϳ5-fold higher than that with Delta4-Fc, and the fold increases in the cell number after the 3-wk culture were 45.7 Ϯ 31.6-fold (n ϭ 11). To confirm that the NK cell differentiation was Notch dependent, we added a ␥-secretase inhibitor, DAPT, which strongly inhibits ligand-dependent Notch activation (24,25). The cells cultured on Delta4-Fc-coated plates in the presence of DAPT had the same immunophenotype as those cultured on the control Fc-coated plates and did not give rise to NK cells (Fig.…”
Section: Human Cb Cd34 ϩ and Cd133 ϩ Cells Gave Rise To Functional Nkmentioning
confidence: 99%
“…Studies of several signaling pathways, as well as transcription factors, have revealed genes involved in the patterning the nephron including Fgf8 (Grieshammer et al, 2005), Pou3f3 (Nakai et al, 2003),Sprouty (Basson et al, 2005;Basson et al, 2006), Notch/presenillins (Cheng et al, 2007;Cheng et al, 2003;McCright et al, 2002), and Lhx1 (Kobayashi et al, 2005). In particular, genetic studies have shown several members of the Wnt family of lipidmodified secreted glycoproteins have important roles in the initiation and maintenance of nephron formation and branching morphogenesis Kispert et al, 1998;Majumdar et al, 2003;Stark et al, 1994).…”
Section: Screen For Genes In Nephron Formationmentioning
confidence: 99%
“…Because both cell types share common melanin synthesis pathway, we decided to investigate whether PS is also required for the pigmentation of mouse cutaneous melanocytes by using specific PS inhibitors (34,35). We cultured primary melanocytes from newborn WT C57BL͞6J mouse skin and allowed the culture to mature and become pigmented (Fig.…”
Section: Ps Are Required For Pigmentation Of Retinal Pigment Epithelimentioning
confidence: 99%